2021
DOI: 10.1002/nml.21464
|View full text |Cite
|
Sign up to set email alerts
|

Institutional antecedents of public service motivation: Administrative regime and sector of economy

Abstract: New findings on public service motivation in the public sector often contradict the previous ones. Such deviations are regularly explained by the uniqueness of the institutional settings of the sample. Yet, only few studies have compared PSM across different institutional environments; even less is known about nonprofit employees. We can only speculate that their institutional antecedents of PSM resemble their public counterparts because of the public benefit orientation of their work. Utilizing a Most Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…It is important to know where in the world the POS studies were conducted because different national and regional institutions can differently affect POS, just as with other perceptions of public and nonprofit employees, for example, their public service motivation (Prysmakova, 2021b). From the perspectives of institutions, we observe two dominant frames of global POS research: Anglo-American and Asian.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to know where in the world the POS studies were conducted because different national and regional institutions can differently affect POS, just as with other perceptions of public and nonprofit employees, for example, their public service motivation (Prysmakova, 2021b). From the perspectives of institutions, we observe two dominant frames of global POS research: Anglo-American and Asian.…”
Section: Resultsmentioning
confidence: 99%
“…Public service motivation. On the contrary, intrinsic rewards were proven to be crucial in motivating public and nonprofit employees (Prysmakova, 2021a(Prysmakova, , 2021b. Even though the relationships between POS and public service motivation are not well examined, some studies show that individual public service motivation connects with employees' perceptions of their organization as good or bad, and it affects its perceived fairness (Wang and Seifert, 2020).…”
Section: Correlates To Be Examinedmentioning
confidence: 99%
See 2 more Smart Citations
“…Essentially the individual PSM can be changed, probably promoted by the beneficial external practices or environmental influence [27]. Recently, some relevant empirical researches have confirmed that the leadership style is a powerful element of the influence on subordinate PSM [28,29]. For example, Bellé (2014) emphasized the relationship between transformational leadership and PSM [30].…”
Section: Introductionmentioning
confidence: 99%